Optimization of the food distribution process using the goal programming technique - Godoi, Letícia Ferreira [UNESP]; Aranha, Flávia Queiroga [UNESP]; Coral, Mariele Colletti; Cantane, Daniela Renata [UNESP] (Springer Nature, 2025)
Food banks play a crucial role in the combat against hunger and food insecurity, being responsible for distributing donated food to the population who are facing restrictions in their access to food. This process presents several challenges in terms of adopting the principles of equity, efficiency, and effectiveness, including when the amount of food available is insufficient to meet all demands. In this context, this study proposes an optimization model using the goal programming technique applied to food distribution in search of improved agility and equity in the process. The model was implemented and analyzed using a fictional scenario and also applied to a realistic scenario that describes the operation of a Brazilian food bank. The results indicate that Chebyshev goal programming is effective in optimizing the distribution process, and promoting equity and efficiency in the assistance provided to social institutions. This approach is an important tool to help managers develop agile process planning strategies.
Keywords: Food banks; Food distribution; Goal programming; Optimization